2014
DOI: 10.1111/his.12344
|View full text |Cite
|
Sign up to set email alerts
|

Low concordance of biomarkers in histopathological and cytological material from breast cancer

Abstract: Our findings suggest that routine clinical ICC and IHC evaluations of predictive biomarkers produce discordant results. Consequently, basing therapeutic decisions on cytology with cut-offs defined for IHC induces a risk that patients will receive suboptimal therapy. However, our analysis shows that local adjustments to biomarker cut-off levels may improve congruency and increase the probability of correct classifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 63 publications
(139 reference statements)
2
27
2
Order By: Relevance
“…Importantly, in this study, ER assessments by cytology and consecutive tumour resections showed high concordance (96.5%–98.5%). However, previous results from our laboratory have shown 9% discordance between ICC and IHC-assessed ER using the same cut-off ≥1% 12. This discrepancy could be explained by a smaller sample size in the previous study (eligible patients for ER comparison n=133).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Importantly, in this study, ER assessments by cytology and consecutive tumour resections showed high concordance (96.5%–98.5%). However, previous results from our laboratory have shown 9% discordance between ICC and IHC-assessed ER using the same cut-off ≥1% 12. This discrepancy could be explained by a smaller sample size in the previous study (eligible patients for ER comparison n=133).…”
Section: Discussionmentioning
confidence: 62%
“…This dual analysis provides a unique opportunity to investigate and compare the diagnostic efficacy of both methods. Related to this, we have previously shown that Ki67 and other predictive biomarkers differ in preoperative fine-needle aspiration cytology compared with resected primary breast tumours 12. The aims of the present study were to investigate the concordance of consecutive biomarker assessment in invasive breast tumours performed on preoperative fine-needle aspiration cytology using ICC and on the tumour resection specimen using IHC, and to investigate concordance with molecular subtype and outcome with both methods.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, mitotic rate is only modestly reproducible between different observers, and varies according to sampling technique, cold ischaemia time, tissue fixation procedures, and the pathologists' time pressure and adherence to guidelines . In addition, Ki67 suffers from interlaboratory discordance, variable prognostic power, and variance in analytical practice, including a lack of standardisation regarding what tumour region to score and what cutoff to apply for high versus low proliferation . In fact, consensus guidelines are considered to be unreliable outside individual laboratories' own reference data …”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, assessments of biomarker status struggle with intra-and interobserver variability, as well as discordance with the gene expression tests. 11,12 This is perhaps especially evident for Ki67 [13][14][15] as there is no consensus on what tumor region or number of cells to score 13,16,17 and what cutoff values for the proportion of positive cells (Ki67 index) distinguish highly from lowly proliferative tumors. In fact, even the consensus guidelines that do exist have been considered unreliable outside individual laboratories' own reference data.…”
mentioning
confidence: 99%